Optical and Structural Properties of Titanium Dioxide Films from and Starting Materials Annealed at Various Temperatures - Shih-Chang Shei (Advances in Materials Science and Engineering)
We investigated the optical and structural properties of titanium dioxide films deposited from and starting materials by electron beam evaporation at annealing temperatures from to . We find that the refractive index of as-deposited films from starting material is higher than that of as-deposited films from starting material. In addition, during thermal annealing, the refractive index fluctuates slightly as compared with films from starting material. This should be attributed to the fact that the deposited molecules had a higher packing density, such that the film was denser. The transmittance spectra of films from starting material indicate that transmittance edge slightly shifts to longer wavelength with the annealing temperature increasing when compared with starting material, in which the transmittance spectra indicate that the transmittance edge strongly shifts to longer wavelength with the same annealing temperature increasing. These findings should be attributed to the absence of oxygen and scattering of rough surface.